Prenatal diagnosis and surgical treatment of vascular rings - A. Pavlova; A. Kurkevich; N. Rudenko; R. Yemec; Tamo Raad; O. Datsko (Ukrainian Journal of Cardiovascular Surgery, 2018)
Vascular rings (VR) are a group of congenital anomalies of the vessels of the aortic arch (AA) that compress the trachea and the esophagus. It causes respiratory symptoms or problems with swallowing. In the period from 2012 to 2015 we diagnosed 28 cases of VR. The primary examination of pregnant women was conducted from the 20th to the 38th weeks of gestation. Right aortic arch with left ductus arteriosus and aberrant left subclavian artery (RAA, LDA, ALSA) was diagnosed in 24 cases. The double aortic arch (DAA) was diagnosed in 4 cases. Among the 28 diagnosis the VR was isolated in 20 and associated with other structural congenital heart disease (CHD) in 8 cases. The diagnosis of VR was took after 1 prenatal and 2 postnatal echocardiograms in 3 cases off. Two children died after birth from non-cardiac causes. Among the 23 diagnoseis the VR was confirmed on the computed tomography angiography (CTA) in 17 (73.9%) cases. However, the different anatomical variants of the VR was complete confirmed in 11 (64,71%) cases and a partial discrepancy was found in 6 (35,29%) cases. Six (26,1%) patients had no symptoms, therefore CT was postponed. Surgical treatment of VR was performed in 13 (56.52%) patients.Articles and own analysis show that CT is the best method in diagnostics VR, but prenatal echocardiography can detect VR during pregnancy. It makes possible to make important additional examinations and helps to improve the treatment.